Tamil migrant women’s perception of a transcultural dietetics tool for the counseling of gestational diabetes patients - Sadeghi,Leila (2017)
Introduction: The Tamil population is one of the largest migrant groups living in Switzerland and presents a high prevalence of gestational diabetes. The changes in dietary patterns due to migration are often underestimated in dietetics counseling. The project NutriGeD from Bern University of Applied Sciences aimed at developing the first official tool, the “Migmapp©”, in Switzerland to help healthcare professionals counsel in the most efficient manner their gestational diabetes patients of Tamil origin. Objectives: The aim of the present study was to assess the perceptions regarding the clarity and usefulness of the MigMapp©s tools among Tamil migrant women living in Switzerland. Methodology: A SurveyMonkey-based questionnaire was developed in German and translated into Tamil. Hardcopies of the survey were distributed to 100 Tamil women living in Switzerland. The completed surveys were manually collected and inserted into SurveyMonkey by NutriGeD team members and analyzed using SPSS and Excel. Results: 76% of the 25 participants had been living in Switzerland for more than 5 years, and 32% had already been diagnosed with gestational diabetes. The majority of respondents (83%, n=20) considered the Migmapp© to be complete in terms of providing the necessary information on the topic of dietetics and exercise tips for gestational diabetes. Both tools rated as the most understandable included a series of depicted visuals with respectively descriptive or instructional text. Helpfulness of using visuals was also shown by the high rating of the diabetic-friendly recipes, each including a photographed standard portion of the menu. Conclusions: Overall, the Migmapp© ; was well accepted among the Tamil women participating in this evaluation survey and considered to be a good provider of lifestyle tips in case of gestational diabetes. The Migmapp© will be further tested for its efficacy and if proven successful, the developed materials will be made available, and developed for other migrant groups.